Reducing handover latency in mobile IPv6-based WLAN by parallel signal execution at layer 2 and layer 3 - Abdullah, Abdul Hanan (Springer-Verlag, 2011)
The emergence of wireless networking demands continuous connectivity to support end-to-end TCP or UDP sessions. Wireless networking does not provide reliable connections to mobile users for real-time traffic such as voice-over IP, audio streaming and video streaming. Handover latency in Mobile IPv6 is one factor that disconnects users while roaming. Most of the proposed methods to reduce handover latency include either layer 2 or layer 3 design considerations. This paper discusses the mobile IPv6 handover process and proposes an efficient handover scheme for reducing the overall handover latency in Mobile IPv6. The proposed scheme consists of parallel signal execution at the access router while the mobile node is performing layer 2 handover. Simulation results shows that the proposed scheme performs better than the standard MIPv6 delays.